Experimental Study on Axial Compression Behavior of Molybdenum Tailings Concrete Column Confined by GFRP - Jian Yuan; Xin Zhao; Lianmin Tian; Zhaolong Hou; Yunfeng Pan; Jun He (Buildings)
To promote the application of molybdenum tailings as the fine aggregate in concrete in construction engineering and verify the feasibility of fiber-reinforced polymer (FRP) material for strengthening molybdenum tailings concrete columns, this study takes a short circular molybdenum tailings concrete column reinforced by glass FRP (GFRP) as the research object. The influences of the molybdenum tailings content (0%, 25%, 50%, 75%, and 100%), the concrete grade (C30, C40, and C50), and the layer number (0, 1, and 2) of the GFRP sheet on the axial compressive capacity of the molybdenum tailings concrete column are investigated. The experimental phenomena and failure modes of the unreinforced and GFRP-reinforced columns are analyzed. The axial compressive strengths of the unreinforced and GFRP-reinforced columns are then compared. The load–strain curve and load–displacement curve of typical molybdenum tailings concrete columns are presented. Subsequently, six classical strength models for FRP-reinforced concrete are used to calculate the axial compressive strength of the confined specimens. The results show that the best classical model has a predictive accuracy with an absolute relative deviation (ARD) of 8.5%. To provide a better prediction of the compressive strength of the GFRP-reinforced molybdenum tailings concrete column, the best classical model is further improved, and the ARD of the modified model is only 5.87%.